2015
DOI: 10.1016/j.arcped.2014.10.025
|View full text |Cite
|
Sign up to set email alerts
|

Étude prospective de l’écologie virale hivernale dans un service de réanimation pédiatrique

Abstract: We have confirmed the frequency of RSV infections in a PICU and found that many patients without respiratory symptoms have respiratory infections caused by viruses. The impact of these infections on patient outcome should now be analyzed in order to demonstrate the role played by respiratory viruses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
0
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 17 publications
1
0
0
Order By: Relevance
“…The pathogens identified in our PICU were similar to those in previous studies in the PICUs (9-11) and general ward (1). Additionally, a high pathogen identification rate of 61% in our study using mPCR testing is similar to that reported previously (64-82%) in other studies (11,12).…”
Section: Use Of Antibiotics and Broad-spectrum Antibiotics And The Le...supporting
confidence: 92%
“…The pathogens identified in our PICU were similar to those in previous studies in the PICUs (9-11) and general ward (1). Additionally, a high pathogen identification rate of 61% in our study using mPCR testing is similar to that reported previously (64-82%) in other studies (11,12).…”
Section: Use Of Antibiotics and Broad-spectrum Antibiotics And The Le...supporting
confidence: 92%
“…In children, bronchiolitis and pneumonia are the most common causes of LRTI and are induced by a large and heterogeneous group of infectious agents, including bacteria, virus, and other aetiologies. Viral infections are the main causes, dominated by HRV and RSV [14][15][16][17][18], but bacterial co-infections are not rare [18,19]. The microbiological diagnosis of these infections, especially the proof of bacterial infection, is difficult to obtain.…”
Section: Introductionmentioning
confidence: 99%